A Novel Supercritical CO2 Foam System Stabilized With a Mixture of Zwitterionic Surfactant and Silica Nanoparticles for Enhanced Oil Recovery - Li, Weitao; Wei, Falin; Xiong, Chunming; Ouyang, Jian; Shao, Liming; Dai, Mingli; Liu, Pingde; Du, Dongxing (Frontiers in Chemistry, 2019)
In order to improve the CO2 foam stability at high temperature and salinity, hydrophilic silica nanoparticles (NPs) were added into a dilute zwitterionic surfactant solution to stabilize supercritical CO2 (SC-CO2) foam. In the present paper, the foaming capacity and stability of SC-CO2 foam were investigated as a function of NP concentration at elevated temperatures and pressures. It was observed that the drainage rate of SC-CO2 foam was initially fast and then became slower with NPs adsorption at the gas-liquid interface. The improved foam stability at high temperature was attributed to the enhanced disjoining pressure with addition of NPs. Furthermore, an obvious increase in the foam stability was noticed with the increasing salinity due to the screening of NP charges at the interface. The rheological characteristics including apparent viscosity and surface elasticity, resistance factor, and microstructures of SC-CO2 foam were also analyzed at high temperature and pressure. With addition of 0.7% NPs, SC-CO2 foam was stabilized with apparent viscosity increased up to 80 mPa·s and resistance factor up to 200. Based on the stochastic bubble population (SBP) model, the resistance factor of SC-CO2 foam was simulated by considering the foam generation rate and maximum bubble density. The microstructural characteristics of SC-CO2 foam were detected by optical microscopy. It was found that the effluent bubble size ranged between 20 and 30 μm and the coalescence rate of SC-CO2 foam became slow with the increasing NP concentration. Oscillation measurements revealed that the NPs enhanced surface elasticity between CO2 and foam agents for resisting external disturbances, thus resulting in enhanced film stability and excellent rheological properties.